UTILIZATION OF INTERACTIVE MEDIA IN THE PROCESS OF LEARNING PKN GRADE I BY TEACHERS AT MI MUHAMMADIYAH BASIN - Arifa, Dian Nur; Sularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
One of the problems of education quality in Indonesia is the learning methods used by teachers are not interesting. The lack of interesting learning often makes students unenthusiastic about teaching and learning activities. In reality, currently in the field there are still many who have not used or are able to apply good learning methods. The purpose of this study was to determine the use of interactive media in the learning process of PKN class 1 by teachers at MI Muhammadiyah Basin. The research method used is qualitative descriptive. At the school, teachers use interactive media in the form of role play, singing, puzzles and utilize technology by using the Wordwall and Quizizz applications. Class 1 at MI Muhammadiyah Basin uses Wordwall for classroom learning. Students are very enthusiastic when learning in class uses Wordwall. Overall, the application of interactive learning media at MI Muhammadiyah Basin shows positive results in improving the quality of education.